XENOFEMINISM AND THE FUTURE OF WORK: REIMAGINING GENDER IN THE AGE OF AI - Tuhfatul Mubarokah Assalamah; Rahma Sugihartati; Muhammad Saud (JISO : Journal of Industrial and Systems Optimization, 2025)
ABSTRAK Perdebatan tentang gender, teknologi, dan feminisme berkembang dengan hadirnya konsep xenofeminisme yang mengkritik persinggungan struktur patriarkal dan kapitalisme teknologi, terutama dalam dunia kerja yang dipengaruhi kecerdasan buatan (AI) dan otomatisasi. Studi ini menelaah bagaimana xenofeminisme, sebagaimana dirumuskan oleh Hester dan Laboria Cuboniks, menawarkan kerangka respons terhadap ketimpangan gender yang diperparah oleh perkembangan teknologi. Melalui tinjauan sistematis berpedoman pada protokol PRISMA atas literatur akademik di basis data Scopus dan analisis tematik, temuan menunjukkan keberlanjutan bias gender dalam sistem AI yang tercermin pada rendahnya keterwakilan perempuan dalam kepemimpinan AI, kesenjangan upah, dan diskriminasi algoritmik. Stereotip sosial serta hambatan pendidikan juga menghalangi partisipasi perempuan di bidang AI. Analisis ini menegaskan potensi xenofeminisme untuk membongkar biner gender dan memanfaatkan teknologi guna menantang norma yang mapan, seraya mendorong perubahan sistemik demi inklusivitas dan keadilan. Studi ini menyimpulkan bahwa kesetaraan AI menuntut keragaman gender dalam tim pengembang, praktik desain peka gender, serta reformasi struktural di pendidikan dan kebijakan kerja, menjadikan xenofeminisme kerangka teoretis penting bagi perubahan sosial transformatif. ABSTRACT Debates on gender, technology, and feminism have advanced with the emergence of xenofeminism, which critiques the convergence of patriarchal structures and technological capitalism, especially within workplaces shaped by artificial intelligence (AI) and automation. This study examines how xenofeminism, as articulated by Hester and the Laboria Cuboniks collective, offers a framework to address gender inequalities intensified by technological developments. Employing a systematic review guided by PRISMA protocols, we analyzed scholarly literature indexed in Scopus using thematic analysis to explore intersections among gender, technology, and labor. The findings indicate persistent gender bias in AI systems, evidenced by women’s underrepresentation in AI leadership, wage disparities, and algorithmic discrimination. Societal stereotypes and educational barriers further constrain women’s participation in AI-related fields. The analysis underscores xenofeminism’s potential to unsettle gender binaries and mobilize technology to contest entrenched norms, while advocating systemic reforms to enhance inclusivity and justice. We conclude that equitable AI requires greater gender diversity in development teams, gender-sensitive design practices, and comprehensive structural changes in education and workplace policies, positioning xenofeminism as a critical framework for transformative social change